Lysosomal membrane-permeabilization (LMP) and -rupture (LMR) are distinct for cell death - Yamashima, Tetsumori (Frontiers in Cell Death, 2025)
Lysosome is crucial for maintaining cellular homeostasis, but disintegrity of its limiting membrane affects the cell death fate. From 1972 to 1999, via the cytochemistry of cultured cells which were exposed to stresses, Brunk et al. defined lysosomal membrane permeabilization (LMP) as leakage through the ultrastructurally-intact limiting membrane. In 1996, via the electron microscopic analysis of the monkey hippocampal CA1 neurons after transient ischemia, Yamashima et al. first identified lysosomal membrane rupture (LMR) as an apparent disruption of the limiting membrane. To elucidate the mechanism of lysosomal cell death, it is indispensable to precisely differentiate LMP and its extensive form LMR. LMP indicates formation of ultrastructurally-undetectable, tiny pores at the lysosomal limiting membrane that allow selective leakage of lysosomal contents. LMP contributes to amplification of the cell death signal, and participates in apoptosis. In contrast, LMR indicates presence of larger holes that cause acute and massive leakage of hydrolytic cathepsin enzymes. LMR leads to the rapid and explosive vanishment of lysosomes, which proceeds along with vanishment of cells, i.e., necrosis. Each representative form of cell death is carried out in human diseases, depending upon the size and number of perforations, the amount of leakage, and the cellular context. The modality of the lysosomal membrane disintegrity, LMP or LMR, determines the cell death fate. It is likely that apoptosis occurs by the proteolytic activation of caspases via LMP, whereas necrosis occurs by the calpain-cathepsin cascade via LMR. This paper is to review ultrastructural evidences of LMR which were identified in diverse pathologic conditions of C. elegans, mice, monkeys, and humans. For elucidating mechanisms of each cell death in the organs affected by stresses, LMP and LMR should be precisely differentiated by electron microscopy. Herein, other lysosomal cell death such as pyroptosis and ferroptosis was discussed to make the difference clear. Ferroptosis might share very similar calpain-cathepsin cascade with necrosis.